Horrie the hoarder - Smyth, Gwenda (Nelson Australia South Melbourne, 1994)
Horrie the Hoarder by Gwenda Smyth is a captivating children$1 (Bs book that tells the story of Horrie, a young boy with a penchant for collecting everything he finds. His room is filled to the brim with toys, trinkets, and treasures, which leads to humorous situations and challenges in his daily life. As Horrie grapples with the consequences of his hoarding, he embarks on a journey of self-discovery, learning the value of organization, sharing, and the importance of relationships over material possessions. With charming illustrations and a relatable storyline, the book encourages young readers to find joy in simplicity and the benefits of decluttering.s